Carboline alkaloids and isocoumarins from the wasp pathogenic fungus Ophiocordyceps sphecocephala BCC 2661. (October 2018) - Kornsakulkarn, Jittra; Saepua, Siriporn; Veeranondha, Sukitaya; Rachtawee, Pranee; Isaka, Masahiko; Thongpanchang, Chawanee
Graphical abstract: Highlights: The constituents of fungus Ophiocordyceps sphecocephala BCC 2661 were investigated. Five new and two new naturally occurring sphecolines A–G were isolated. Three known β -carboline alkaloids and four known isocoumarins were also isolated. Sphecolines A and C exhibited cytotoxic activity against NCI-H187 cell lines. Abstract: Ten β -carboline alkaloids, including five new and two new naturally occurring compounds, sphecolines A–G (1 –7 ), together wit2h four known isocoumarins were isolated from a wasp-pathogenic fungus Ophiocordyceps sphecocephala BCC 2661. Structures of these compounds were determined by NMR spectroscopic and MS spectrometric analyses. Sphecolines A (1 ) and C (3 ) exhibited cytotoxic activity against human small-cell lung cancer NCI-H187 cell lines, with IC50 values of 79.9 and 75.1 μM, respectively.